Dosimetry assessment of DNA damage by Auger-emitting radionuclides: Experimental and Monte Carlo studies. (November 2017) - Di Maria, S.; Belchior, A.; Pereira, E.; Quental, L.; Oliveira, M.C.; Mendes, F.; Lavrado, J.; Paulo, A.; Vaz, P.
Abstract: Recently there has been considerable effort to investigate the potential use and efficacy of Auger-electron emitters in targeted radiotherapy. Auger electrons travel a short distance within human tissues (at nano-scale level) and, therefore, if an Auger-emitting radionuclide is transported to the cell nucleus it will cause enhanced DNA damage. Among the Auger-emitting radionuclides, 125 I is of particular interest, as it emits about 25 electrons per decay. 99m Tc only emits 5 electrons per decay, but presents some attractive characteristics such as a short half-life, easy procurement and availability and ideal imaging properties for therapy monitoring. In order to study the dosimetric behavior of these two radionuclides ( 125 I and 99m Tc) at nano-scale sizes and given the DNA-intercalation properties of Acridine Orange (AO), we have designed 99m Tc (I)-tricarbonyl complexes and 125 I-heteroaromatic compounds that contain AO derivatives, in order to promote a closer proximity between the radionuclides and the DNA structure. With the aim to have an insight on the relevance of these radiolabelled compounds for DNA-targeted Auger therapy, different aspects were investigated: i) their ability to cause DNA strand breaks; ii) the influence of the two different radionuclides in DNA damage; iii) the effect of the distance between the AO intercalating unit and the radioactive atom ( 99m Tc or 125 I). To address these issues several studies were carried out encompassing the evaluation of plasmid DNA damage, molecular docking and nanodosimetric Monte Carlo modelling and calculations. Results show that the two classes of compounds are able to induce DNA double strand breaks (dsb), but the number of DNA damages (e.g. dsb yield) is strongly dependent on the linker used to attach the Auger emitting radionuclide ( 125 I or 99m Tc) to the AO moiety. In addition, nanodosimetric calculations confirm a strong gradient of the absorbed energy with the DNA-radionuclide distance for the two radionuclides studied. Finally these results show the existence of a critical distance (of about 11 Å) beyond which it is probable that the direct effects start to be ineffective in DNA damage induction. Highlights: Study of potential use of Auger electron emitters in targeted radiotherapy. Evaluate the dosimetric behavior at nano scale of 125 I and 99m Tc radionuclides. Ability for these two radionuclides to produce double strand breaks (dsb). Both radionuclides are able to induce DNA damages depending on the linker used. Critical distance (of about 11 Angstrom) for direct and indirect DNA damage effects.